(untitled) (Global Journal of Science Frontier Research, 2012)
In this report, a hybrid power system has been designed considering photovoltaic, wind turbine generator and diesel generator. HOMER software has been used for analyzing the performance of the system. Different performance analysis like feasibility, sensitivity, cost, and sustainability has been done. Environmental and economic analysis is used to discuss the sustainability of a hybrid power system. Primary ac loads for 24 hours, solar resource and wind resource inputs for a year are used. Analysis reveals that the hybrid system with photovoltaic, diesel generator, wind turbine give better performance in terms of cost and sensitivity.